Effect of Cathodic Voltage on Structural, Optical, and Surface Properties of Electrodeposition of CdZnTe Thin Film for Optoelectronic Applications - Ahmed Umer Yimamu; Fekadu Tolessa Maremi; Solomon Zerihun Werta; Francis Birhanu Dejene; Ibrahim Mohammed Beker; Vanthini Nelson Adoons; Megersa Kassim Hussen; Selepe Joel Motloung; Jacobus J. Terblans (Ethiopian Journal of Science and Sustainable Development)
This study investigated the impacts of varying growth voltage on structural, optical, and surface characteristics of electrodeposited cadmium zinc telluride (CdZnTe) thin films. The electrodeposition was performed using a potentiostatic mode with a cheap two-electrode electrodeposition method. The production of the thin films took place at deposition voltages of 1700, 1750, 1800, and 1850 mV. X-ray diffraction (XRD), ultraviolet-visible (UV-Vis) spectroscopy, and scanning probe microscopy (SPM) were used to evaluate the features of CdZnTe thin films. The XRD analysis confirmed that polycrystalline cubic CdZnTe structures with (111) preferential orientation were detected. The maximum crystallite size, minimum dislocation density, number of crystallite sizes per unit area, and microstrain were recorded at 17500 mV growth voltage. The UV-Vis analysis revealed that the energy bandgap of CdZnTe thin films varied increased from 1.55 to 2.05 eV as the deposition voltage increased from 1700 to 1850 mV. Utilizing a cathodic voltage of 1750 mV, the highest average surface roughness measured was 52.15 nm. Thus, a deposition voltage of 1750 mV can be used as the optimized voltage for the growth of CdZnTe thin film, and it has potential applications for thin film-based solar cell devices.